2013
DOI: 10.1080/03055698.2012.671514
|View full text |Cite
|
Sign up to set email alerts
|

Emotional intelligence and negative feelings: a gender specific moderated mediation model

Mehmet Karakuş

Abstract: This study aims to clarify the effect of emotional intelligence (EI) on negative feelings (stress, anxiety, burnout and depression) in a gender specific model. Four hundred and twenty-five primary school teachers (326 males, 99 females) completed the measures of EI, stress, anxiety, burnout and depression. The multi-group analysis was performed using a structural equation approach. The moderated mediation results show that there are gender related differences in the relationships of age, emotional intelligence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 49 publications
2
30
0
3
Order By: Relevance
“…Stress Scale: The scale was developed by Karakuş (2013). The scale consists of one dimension and four items.…”
Section: Data Collection Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stress Scale: The scale was developed by Karakuş (2013). The scale consists of one dimension and four items.…”
Section: Data Collection Toolsmentioning
confidence: 99%
“…Assessment of the scale is in the form of a five-point Likert scale. Karakuş (2013) calculated the internal consistency coefficient of the scale as .70. The Stress Scale was rated between (1) absolutely disagree and (5) completely agree.…”
Section: Data Collection Toolsmentioning
confidence: 99%
“…People with high emotional intelligence can focus on an established goal while maintaining a high degree of enthusiasm and can skillfully use emotional information to solve problems encountered in work or life (Mayer & Salovey, 1993;Tsaousis & Nikolaou, 2005). Emotional intelligence has been determined to be a superior predictor of occupational burnout (Alavinia & Ahmadzadeh, 2012;Baik & Yom, 2012;Karakuş, 2013;Weng et al, 2011). Improving emotional intelligence can reduce the incidence of chronic stress developing into occupational burnout (Görgens-Ekermans & Brand, 2012;Mansoor, Amir, Pooran, & Masood, 2011).…”
Section: Moderating Effect Of Emotional Intelligencementioning
confidence: 99%
“…Law, Wong, and Song () confirmed that emotional intelligence was conceptually a distinct personality trait, consisting of a set of abilities that a person can use to understand, regulate, and make use of his or her emotions, and that it can be learned and modified. Employee emotional intelligence has also been associated with turnover in education and manufacturing with increasing employee emotional intelligence correlated with decreased burnout and lower turnover rates (Alavinia & Ahmadzadeh, ; Jordan & Troth, ; Karakus, ). Research on the relationship between staff nurse emotional intelligence and retention/turnover is very limited, but initial findings suggest that emotional intelligence correlate positively with both performance level and retention (Codier, Kamikawa, Kooker, & Shoultz, ) and that improving emotional intelligence reduces the incidence of chronic stress and occupational burnout (Mansoor, Fida, Nasir, & Ahmad, ).…”
Section: Introductionmentioning
confidence: 99%